2010
DOI: 10.1155/2010/184137
|View full text |Cite
|
Sign up to set email alerts
|

Mild Hydrothermal Synthesis of Ni–Cu Nanoparticles

Abstract: Magnetic Ni-rich Ni–Cu nanoparticles with Ni : Cu mass ratio (S) of 2.0 and 2.6 were prepared using a mixture of polyoxyethylene (10) isooctylphenyl ether (Triton X-100) and sodium dodecyl sulfate (SDS) in a mild hydrothermal condition at 95ºC. X-ray diffractometry (XRD) showed that the nanoparticles prepared atS=2.0possessed Ni–Cu alloy characteristic whereas the characteristic was absent atS=2.6. The XRD data was enhanced by Fourier transform infrared spectroscopy (FTIR) which exhibited metal-metal (Ni–Cu) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Moreover, the positive shift of the Ni-rich phase in the Ni-Cu alloy peaks from 43.7° for 5%Ni5%Cu/C to 44.3° for 10%Ni10%Cu/C indicated a higher Ni proportion in the shell region of the surface, according to Vegard's law[59][60]. Similar results were reported by other research groups[61][62][63] that observed different segregation characteristics for a specific Ni:Cu composition by changing the synthetic method. In our case, the same effect was obtained by changing the metal loadings.…”
supporting
confidence: 87%
“…Moreover, the positive shift of the Ni-rich phase in the Ni-Cu alloy peaks from 43.7° for 5%Ni5%Cu/C to 44.3° for 10%Ni10%Cu/C indicated a higher Ni proportion in the shell region of the surface, according to Vegard's law[59][60]. Similar results were reported by other research groups[61][62][63] that observed different segregation characteristics for a specific Ni:Cu composition by changing the synthetic method. In our case, the same effect was obtained by changing the metal loadings.…”
supporting
confidence: 87%
“…The slight shift in diffraction peaks of bimetal Ni–Cu from the standard Ni and Cu crystalline peaks shows the formation of an alloy. The solvothermal treatment for reduction of the catalyst was done, which may lead to Ni–Cu alloy formation . The small additional peak at 24.32° (002) could be attributed to the reduced graphene oxide in Ni–Cu@RGO while, the characteristic peak at 10° (001) disappears in the XRD pattern (see Figures b and c).…”
Section: Resultsmentioning
confidence: 99%
“…Also, they showed lower activation energy. Moreover, the present nanofibers containing magnetic element Ni, so nanofibers can be separated easily from the solution and reused [39]. The introduced nanofibers revealed a good stability toward hydrogen release from AB.…”
Section: Introductionmentioning
confidence: 87%